Supply, Storage, and Service Reliability Decisions by Gas Distribution Utilities: A Chance-Constrained Approach: Comments on Guldmann's Paper - Rasmussen, Jill J. (Management Science, 1983)
A question has been raised as to the value of Guldmann's paper because the model application indicates very small increments of benefits over costs for the “optimal” decision across a wide range of “nonoptimal” ones. That is, no matter what decision is made about storage capacity or reliability level, savings are on the order of 1 percent of costs. In addition, similar increments of benefit occur irrespective of conversion capacity or reliability level.